دراسة عنصر التحمل لدى لاعبي كرة القدم خلال المرحلة التحضيرية لأندية الساحل السوري (Latakia University Journal -Medical Sciences Series, 2016)
Increasing and improving general and basic specific endurance at the preparatory phase of the football players are perceived as one of the greatest factors that contribute to successful and effective application of training programmes. Additionally, it helps improve players’ capabilities to endure the league's pressure. More specifically, it is worth noting that the football players need additional or exceptional efforts during the national league. Furthermore, the football matches at the national and international levels may exceed 80 every season, which raises the importance of the endurance element. This study aims to determine the level of endurance element for players from Banias Football Club and Huten Football Club before and after the preparatory phase, and to understand the level of change (improvement) that occurred on this element. Quantitative method was adopted to answer research questions. The results revealed that there are significant differences between the two groups, particularly for Banias Club players. يعتبر تدريب و تحسن عنصر التحمل(العام و الخاص) في مرحلة التكوين و الإعداد(المرحلة التحضيرية) لدى لاعبي كرة القدم من أهم العوامل التي يحب أن تساهم في نجاح البرنامج الزمني التدريبي للمدربين, ويساهم أيضاً في قدرة اللاعبين على تحمل أعباء الموسم الرياضي, حيث أن لاعبو كرة القدم يحتاجون في الآونة الأخيرة إلى بذل أقصى جهد أي عليهم امتلاك تحمل عالي جداً بشقيه(العام و الخاص), اذ أن كثرة الألعاب والمنافسات الرياضية التي يواجهها لاعبو كرة القدم قد تصل في بعض الأحيان إلى أكثر من (80) ثمانين مباراة في الموسم الرياضي الواحد من المواجهة في تنفيذ ألعاب الدوري أو المنتخبات و البطولات المحلية و الخارجية, ويهدف البحث إلى تحديد مستوى عنصر التحمل لدى لاعبي مصفاة بانياس و حطين قبل و بعد الانتهاء من المرحلة التحضيرية والتعرف على مستوى التغير الحاصل في هذا العنصر.وبعد اجراء الاختبار و الانتهاء منه بشكل كامل تم جمع النتائج و معالجتها إحصائياً وعرضها و مناقشتها بأسلوب علمي بغية تحقيق هدف البحث, وفي نهاية البحث توصلنا إلى وجود فروق واضحة بين المجموعتين و لصالح لاعبي مصفاة بانياس.